(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The development of the world of tourism has undergone various changes, both changes in the pattern, shape and nature of activities, as well as the encouragement of people to travel, ways of thinking that can provide rapid economic growth. Tourism development is not only directed at attracting foreign tourists but also domestic tourists. In line with the development of the world of tourism which appears to be increasing, as well as the existence of areas that have the potential to become tourism objects, therefore the selection of activities or development of facilities must be measured in a way that does not conflict with social and ecological values. The purpose of this study was to find out the development of Lembeh Island tourism in Bitung City. The theory used is development and tourism. The research method used is a qualitative method that is trying to find answers to questions related to tourism development. These questions require descriptive answers that describe the facts about the problems being investigated as well as the rational interpretation of various findings in the field while analyzing all the conditions at the research site. Based on the results of the research namely the development of Lembeh Island tourism in Bitung City, some tourist sites have not developed and due to lack of government attention, one of them is the limited facilities available at Lembeh Island tourist attractions in Bitung City. Keywords: Development, Tourism, Island